2017
DOI: 10.1080/0142159x.2017.1408899
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of incentive structure on student participation and performance in active learning strategies: A comparison of case-based and team-based learning

Abstract: Our results suggest that assessments of medical knowledge during active learning exercises could supplement non-cognitive assessments and could be good predictors of performance on summative examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
5
26
0
Order By: Relevance
“…Each student on a TBL team shares the gRAT score independent of their individual contributions to the team discussion. As expected, average gRAT scores are generally higher than average iRAT scores .…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Each student on a TBL team shares the gRAT score independent of their individual contributions to the team discussion. As expected, average gRAT scores are generally higher than average iRAT scores .…”
Section: Introductionsupporting
confidence: 76%
“…In this same study, we also found that iRAT scores, a surrogate for individual student preparation, are lower and do not correlate with final examination scores when TBLs do not contribute to the course grade . In a different study, where we compared two different active learning activities at our institution with different incentive structures, modified case‐based learning (CBL) and TBL, we found that only performance on graded TBL exercises correlated with final examination scores .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Case-based teaching model is an effective teaching method (Reed, & Brunson, 2018). Literature calls for a wider adoption of case-based teaching model (Carrasco, Behling & Lopez, 2018;Singh, Shree & Parahoo, 2018). All the studies pertaining to case-based teaching model in professional and educational domains contend that this method encourages active learning, independent thinking and judgement.…”
Section: Case-based Teaching Modelmentioning
confidence: 99%
“…4 Active participation in learning is more beneficial to students than passive transfer of information; it encourages collaboration, promotes the connection of ideas and concepts, and facilitates retention and recall of information. 5 In addition, during each case there are plenary lectures, workshops and life science sessions which are always in a context relating to the case and are intended to both broaden and focus student knowledge and attitudes. This blend of PBL, situated learning and enquiry-driven "every day" learning stands at the heart of the Peninsula Dental School's enquiry-based learning ethos.…”
Section: Introductionmentioning
confidence: 99%